Ungovernable systems: The strength of informal institutions in the sea cucumber fishery in Yucatan, Mexico. - Carmen Pedroza-Gutiérrez; Jorge A López-Rocha (PLoS ONE)
Formal and informal institutions govern fisheries around the world. Yucatan's sea cucumber fishery is not an exemption, the sudden and fast development of the fishery in 2010 has motivated the creation of informal and illegal forms of organization. The prices, buyers' interest and the fishing effort substantially increased, being followed by illegal fishing-fishers and traders, creating informal fishing-trade channels and severe social and biological concerns. This article aims to give account of the emergence and dynamics of the informal institutions which currently dominate this fishery. It was sought to identify the extent to which rules and regulations are not being respected and how they are affecting fish resources and coastal communities. We considered the case of the port of Sisal, Yucatan, Mexico to illustrate our argument and here we applied a mixture of qualitative and quantitative methodologies including informal and in-depth interviews applied to 17 key informants, a questionnaire applied to 47 fishers and an estimation of the degree of compliance from three of the main management measures. Socio-biological negative impacts were identified in Yucatan's coastal communities and its fisheries. Foreign buyers and local middlemen exert high pressure on fishers to exceed the quota and catch the highest possible volumes facilitating the fisheries decline. This and the growing economic interest motivated the development of strong informal institutions supporting illegal fishing and informal trade. Social problems emerged and women were particularly affected. The economic power of the fishery is likely to overcome any type of governance structure. The enforcement of entry rules was not effective, so the governance base was around informality and illegal actions. Local and foreign buyers are exerting pressure to increase the catch volume thus it is recommended that rules and regulations be directed at buyers and exporting companies rather than at fishers.